Calcifying Odontogenic Cyst - A Case Report - Yadav, Deepak; Tripathi, Shashank; Mishra, Ravish; Panthee, Anuja; Kandel, Santosh; Chakroborty, Bijan Kumar (Journal of Universal College of Medical Sciences, 2018)
The calcifying odontogenic cyst (cocc) is a developmental odontogenic cyst,which was first categorized as a distinct entity by Gorlin in 1962.It is an unusual and unique lesion,which may show characteristics of both a solid neoplasm and a cyst. It usually occurs as an intraosseouslesion but may occasionally occur as an extraosseous or peripheral variant.It shows a newly equal distribution between the maxilla and mandible and is commonly seen anterior to the first molar.The clinical and radiographic features of this lesion are not pathognomic,and it is characterized by its histological diversity,with the most characteristic feature being the presence of a variable number of ghost cells within the epithelial component.Treatment of choice for COC is surgical enucleation which is done in a conservative mannerand recurrences are unlikely. This report describes a case of COC of a 26yrs old female in association with swelling on left side of maxilla since 2 years. Journal of Universal College of Medical Sciences (2016)Vol.04 No.02 Issue 14, page:40-42